2013
DOI: 10.1155/2013/252417
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Surface Modifications of Carbon Nanotubes on the Properties of Polyamide 66/Multiwalled Carbon Nanotube Composites

Abstract: The effects of surface modification of carbon nanotube on the properties of polyamide 66/multiwalled carbon nanotube composites have been investigated. Polyamide 66 (PA66) and multiwalled carbon nanotube (MWCNT) composites were prepared by melt mixing. The surfaces of MWCNTs were modified with acid- and amine-groups. Field emission scanning electron microscopy analyses revealed that amine-MWCNTs (D-MWCNTs) dispersed better in the PA66 matrix than pristine- and acid-MWCNTs. However, an introduction of D-MWCNTs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This is indicative of a nucleating effect caused by the CNTs, which enhances the overall non-isothermal crystallization rate of the PA410 from the melt. This has also been reported for other PA-based NCs [8,10,12,13,28,30].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This is indicative of a nucleating effect caused by the CNTs, which enhances the overall non-isothermal crystallization rate of the PA410 from the melt. This has also been reported for other PA-based NCs [8,10,12,13,28,30].…”
Section: Resultssupporting
confidence: 83%
“…Therefore, PA/CNT NCs are of great interest from an engineering point of view, and have been widely studied in the literature. PA6 is by far the most widely used commercial polyamide in the fabrication of PA/CNT-based NCs [7,8,9], but other PAs such as PA66 [10,11], PA12 [12], PA610 [13], PA1010 [14] or PA11 [15], and less frequently PA46 [16] or PA1212 [17] have also been studied. In these works, the thermal properties of NCs were studied, as well as the effect on the dispersion of CNTs and the mechanical and electrical properties of the NCs of different aspects such as the processing conditions, the condition of the CNTs (pristine or modified), their aspect ratio, and the viscosity of the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In the extensive literature on PA/CNT NCs, PA6 is the commercial polyamide most frequently used in the production of this type of nanocomposite [8][9][10]. However, other PAs, such as PA66 [11,12], PA12 [13], PA610 [14], PA1010 [15], and PA11 [16], and to a lesser extent PA46 [17] and PA1212 [18], have also been studied. It is worth mentioning that articles on bio-based PAs are rare [5,19,20] and studies on bio-PA/CNT NCs are practically non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have reported attempts to reinforce a prosthetic material by using material nets, glass, fabric, nylon fabric, carbon fabric, aramide fabric, and even Kevlar [34,35,36,37,38,39,40]. Although carbon-graphite reinforcements in particular appear to be promising [34,35,36], more in vivo studies are required [37].…”
Section: Resistance To Intraoral Forcesmentioning
confidence: 99%
“…Although carbon-graphite reinforcements in particular appear to be promising [34,35,36], more in vivo studies are required [37].…”
Section: Resistance To Intraoral Forcesmentioning
confidence: 99%